Adoption of Mobile Wallet During Covid-19 Outbreak: The Consumer Perspective - Lim Kah Boon; Yeo Sook Fern; Lim Chiou Fen (Journal of International Business, Economics and Entrepreneurship)
Government authorities have encouraged the public to use the contactless payment method in accordance with the new norm practised during the COVID-19 pandemic outbreak. Malaysians will receive RM50 in mobile wallet credit as part of a Penjana Economic Recovery Plan initiative in July 2020 to encourage safe and contact-free payment. Hence, this paper aimed to study the factors influencing consumer adoption of mobile wallets during the COVID-19 outbreak. The independent variables included in this study are perceived usefulness, perceived ease of use, perceived social influence and perceived security. A total of 250 Malaysians from three states of Malaysia are given a set of self-administered questionnaires to be answered. The response rate is 94%, with 235 sets of completed questionnaires used for analysis. The Partial Least Squares Structural Equation Modelling (PLS-SEM 3.3.3) is used to analyse the model. The hypothesis testing results concluded that perceived usefulness, social influence and perceived security have a significant relationship with mobile wallet adoption during the COVID-19 outbreak. Nonetheless, this research is useful for mobile wallet developers and other researchers. Lastly, the findings of this study provide some managerial implications for mobile wallet developers, which can help developers produce a better mobile wallet in the marketplace.